Peningkatan prestasi siswa materi renang gaya dada melalui penggabungan kekuatan dua orang - Pujianto Pujianto (Patria Educational Journal (PEJ), 2023)
The aims of this study were: (1) to describe the effect of the learning method combining the power of two people on the learning outcomes of Physical Education. (2) Describe how far the understanding and mastery of the Penjasorkes subject is after the application of the Strength of Two Persons Method. The data obtained is in the form of formative test results, observation sheets of teaching and learning activities. This study uses a class action research design. The conclusion from this research is that through the Power of Two Person Combining Method it can have a positive effect on the student learning process, and this learning model can be used as an alternative to Physical Education.